2011
DOI: 10.4067/s0718-19572011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Pathology caused by adult Pseudochondracanthus diceraus (Copepoda:Chondracanthidae), a parasite of bullseye puffer fish Sphoeroides annulatus

Abstract: Resumen.-El copépodo condracántido Pseudochondracanthus diceraus es un parásito frecuente en las branquias del botete diana silvestre, Sphoeroides annulatus en Sinaloa, México. El presente estudio constituye la primera descripción de algunos parámetros sanguíneos y la histología branquial de S. annulatus infestados por hembras adultas de P. diceraus. Se aclimataron sesenta y dos peces silvestres en tanques experimentales por 15 días y a los 16 y 21 días se tomaron muestras para la realización de los análisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…In previous studies on parasitofauna of puffer fishes from the southern of GoM (Vidal-Martínez and Mendoza-Franco 2008;Pech et al 2009), this copepod was not reported. Special attention should be paid to the presence of P. diceraus, which has caused high mortality in the culture of S. annulatus (Fajer-Ávila et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on parasitofauna of puffer fishes from the southern of GoM (Vidal-Martínez and Mendoza-Franco 2008;Pech et al 2009), this copepod was not reported. Special attention should be paid to the presence of P. diceraus, which has caused high mortality in the culture of S. annulatus (Fajer-Ávila et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sphoeroides, há registros de diferentes táxons em várias partes do mundo, incluindo o Brasil(MARTÍNEZ-AQUINO et al, 2020;FAJER-ÁVILA et al, 2011;ÁLVAREZ-BORREGO e FÁJER-ÁVILA, 2006;DYKOVÁ et al, 2002;THATCHER, 2001;VIDAL-MARTÍNEZ e MENDOZA-FRANCO, 2008).Sphoeroides spengleri tem importância ornamental (FROESE e PAULY, 2019), mas 51,8% dos participantes em ambas as comunidades disseram que o peixe é consumido. Os registros científicos de parasitos nestes três táxons de peixes endossam o conhecimento tradicional local.…”
unclassified